NUTRITION FLIPBOOK -BASED EDUCATION ON PREGNANT WOMEN'S ATTITUDES TO PREVENT STUNTING - Srininta; Mesrida Simarmata; Indra Agussamad; Zahara Herani (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2025)
Background​ : Nutrition for 1,000 lives First will filled since child in content until child 2 years old . Negative attitude so inhibitor Because Mother pregnant No know nutrition . Flipbook : information media interesting audio and visual . Objectives : For know effectiveness education based flipbook  1,000 days of nutrition First life to attitude Mother pregnant in prevention stunting . Method : Type of research quantitative , design quasi- experiment t design two group pre post test design . Population: 50 pregnant women undergoing antenatal care at the Medan Denai Community Health Center from January to March 2025. The sample is an inclusion of gestational age <32 weeks, willing to be respondents as many as 40 people. Total sampling technique : A sample of 40 pregnant women was divided into 2 groups: treatment and control using simple random sampling . Research location: Medan Denai Community Health Center. Time: June-September 2025. Pre and post data analysis: Wilcoxon test , for comparison of treatment and control after education using the Mann Whitney test . Results : Treatment: before min- max 13-28 mean 20.90, after min -max 30-35 mean 32.40. Wilcoxon test 0.000. Group control before min- max 12-26 mean 18.45 after min- max 14-27 mean 20.35 Wilcoxon test 0.001. Comparison after the second Mann test group Whitney significant value 0.000 < 0.05 then change attitude group treatment more tall than group control . Conclusion . Education based flipbook effective to change attitude Mother pregnant become positive in prevention stunting